Existence for Eventually Positive Solutions of High-Order Nonlinear Neutral Differential Equations with Distributed Delay - Huanhuan Zhao; Youjun Liu; Jurang Yan (Discrete Dynamics in Nature and Society)
We consider the existence for eventually positive solutions of high-order nonlinear neutral differential equations with distributed delay. We use Lebesgue's dominated convergence theorem to obtain new necessary and sufficient condition for the existence of eventually positive solutions.